Digital Based Estimation of Residential Property Losses from Liquefaction in West Jakarta - Maryati, Indah; Zaki, Muhammad; Pontan, Darmawan; Widiarso, Tulus (Technomedia Journal, 2025)
Liquefaction poses a significant threat to urban areas with water-saturated alluvial soils, especially in seismically active zones like West Jakarta. Using Cone Penetration Test (CPT) data from 25 locations, soil susceptibility was evaluated through Cyclic Stress Ratio (CSR), Cyclic Resistance Ratio (CRR), and Magnitude Scaling Factor (MSF). Areas with safety factor (FS) values below 1 were identified as having high liquefaction potential. Residential buildings were categorized by floor area and assessed using the 2024 Government Property Sales Value (NJOP) to estimate potential financial loss. Structural damage percentages were determined using seismic intensity thresholds and empirical damage functions. Analysis showed that residential areas with moderate to loose soil conditions, particularly in the northern and western zones, are most vulnerable. The total estimated loss reached IDR 189.8 billion, with the highest concentration of damage in medium and large sized residential properties. These findings emphasize the critical need to integrate geotechnical parameters into spatial risk mapping and urban disaster mitigation planning. A digital loss estimation model combining soil characteristics, seismic parameters, and economic valuation provides a scalable approach for early warning systems and resilience-oriented urban planning. The study contributes to data-driven risk management strategies aligned with sustainable development objectives and adaptive infrastructure policies.